KABUPATEN LAYAK ANAK: KEBIJAKAN DALAM MELINDUNGI HAK ANAK DI KABUPATEN CILACAP PROVINSI JAWA TENGAH - Vinda Verina; Dwiki Bayu Pamungkas; Merintha Suryapuspita (Jurnal Kebijakan Pemerintahan, 2023)
Abstract Indonesia is an Emergency Violence Against Children, where from 2019 to 2020 there has been an increase in the number of child protection cases by 33%. The government through the State Ministry for the Empowerment of Women and Children supports efforts to fulfill children's rights through the Child Friendly District Policy. Cilacap district has succeeded in increasing the KLA rating category from middle to junior high, but cases of child abuse in Cilacap district are still very high. From this background, in this study there is how the Implementation of Child-Friendly District Policy in reducing child-bearing rates in Cilacap Regency. This study was designed using a Kualitatif method. Data were obtained through interviews, observation and documentation and were processed using the interactive analysis technique. The study uses the Implementation Theory of Edward III which consists of the dimensions of communication, resources, disposition and bureaucratic structure. The results of the study show that based on the assessment guidelines, the KLA Policy in Cilacap Regency has achieved very good results. However, in terms of child abuse the figures are still fluctuating and difficult to control. Several factors such as APBD funding support, integrated policy development and adequate facilities are supporting factors in the implementation of this KLA policy. However, other factors such as the resources quality of the apparatus and the lack of public understanding of the procedure for servicing cases of child abuse became an inhibiting factor in the implementation of this KLA policy. Abstract Indonesia is an Emergency Violence Against Children, where from 2019 to 2020 there has been an increase in the number of child protection cases by 33%. The government through the State Ministry for the Empowerment of Women and Children supports efforts to fulfill children's rights through the Child Friendly District Policy. Cilacap district has succeeded in increasing the KLA rating category from middle to junior high, but cases of child abuse in Cilacap district are still very high. From this background, in this study there is how the Implementation of Child-Friendly District Policy in reducing child-bearing rates in Cilacap Regency. This study was designed using a Kualitatif method. Data were obtained through interviews, observation and documentation and were processed using the interactive analysis technique. The study uses the Implementation Theory of Edward III which consists of the dimensions of communication, resources, disposition and bureaucratic structure. The results of the study show that based on the assessment guidelines, the KLA Policy in Cilacap Regency has achieved very good results. However, in terms of child abuse the figures are still fluctuating and difficult to control. Several factors such as APBD funding support, integrated policy development and adequate facilities are supporting factors in the implementation of this KLA policy. However, other factors such as the resources quality of the apparatus and the lack of public understanding of the procedure for servicing cases of child abuse became an inhibiting factor in the implementation of this KLA policy. Abstract Indonesia is an Emergency Violence Against Children, where from 2019 to 2020 there has been an increase in the number of child protection cases by 33%. The government through the State Ministry for the Empowerment of Women and Children supports efforts to fulfill children's rights through the Child Friendly District Policy. Cilacap district has succeeded in increasing the KLA rating category from middle to junior high, but cases of child abuse in Cilacap district are still very high. From this background, in this study there is how the Implementation of Child-Friendly District Policy in reducing child-bearing rates in Cilacap Regency. This study was designed using a Kualitatif method. Data were obtained through interviews, observation and documentation and were processed using the interactive analysis technique. The study uses the Implementation Theory of Edward III which consists of the dimensions of communication, resources, disposition and bureaucratic structure. The results of the study show that based on the assessment guidelines, the KLA Policy in Cilacap Regency has achieved very good results. However, in terms of child abuse the figures are still fluctuating and difficult to control. Several factors such as APBD funding support, integrated policy development and adequate facilities are supporting factors in the implementation of this KLA policy. However, other factors such as the resources quality of the apparatus and the lack of public understanding of the procedure for servicing cases of child abuse became an inhibiting factor in the implementation of this KLA policy. Keyword: Child-friendly Districts, Child Violence, Implementation